Acceptability of broadly neutralizing antibodies (bNAbs) for HIV prevention among vulnerable populations in India: Findings from a qualitative study. - Joyeeta Mukherjee; Saif Ul Hadi; Venkatesan Chakrapani; Shruta Rawat; Aylur Kailasom Srikrishnan; Vaishali Mahendra; Dicky Baruah; Shobha Mohapatra; Usha Gopinath; Alpana Dange; Pratyasha Rath; Pallavi Manchi; et al. (PLoS ONE)
With newer advances in HIV biomedical research, the prevention toolbox is expanding with potential inclusion of long-acting anti-retrovirals, broadly neutralizing antibodies (bNAbs), and vaccines. While a multitude of prevention options provide diverse choice sets, they may potentially introduce conundrums and trade-offs which influence end-user decisions on acceptability. Thus, to maximize the unique value and uptake of new products, it is critical to understand contextual drivers of choice and relative product positioning. With HIV bNAbs in the pipeline, a qualitative study was conducted to understand end-users' acceptability. 36 focus-group discussions (n=242) and 57 in-depth interviews were conducted in Chennai, Delhi and Mumbai, with female sex workers (FSWs), men who have sex with men (MSM), people who inject drugs (PWID) and transgender women (TGW) and adolescent girls and young women (AGYW). In addition, 15 simulated behavioral experiments (n=94) were conducted to delve deeper into factors influencing decision-making and potential avenues for intention-action gaps to understand preference construction and reversal pathways. Efficacy, frequency of administration and side-effects were the most important attributes driving acceptability. At least 70% to 90% efficacy was preferred. Arm was the most preferred site of administration (familiarity, maximum privacy), whereas buttocks were preferred by some (better pain tolerance, unhampered mobility). One injection every 3-6 months from community-based facilities was most preferred. Most did not favor self-administration (lack of self-efficacy, adverse events) and voiced confidence in community-friendly professionals. Concerns were raised about potential major side-effects such as interactions with co-morbidities, fertility, pregnancy, gender-affirmation therapy, physical appearance. When end-users were presented with hypothetical product profiles, all preferred the non-antiretroviral (non-ARV) based option which had arm as site of injection and administered every three months by healthcare workers. The preference construction journey revealed positive emotions and rational considerations which favoured bNAbs use but they were contrasted with negative emotions and rationale which hindered acceptability, and the users were faced with multiple conundrums. Some of these conundrums gave rise to potential scenarios of preference reversal.